Conflict and Consensus in The Dynamics of Islamic and Christian Relations in Tolaki Tribe in Indonesia - Alifuddin, Muhammad; Iye, Risman; Abida, Fitriah Inda Nur (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
This study explores the dynamics of interfaith conflict and consensus between Islam and Christianity within the Tolaki community of Konawe, Sulawesi. Despite sharing common cultural roots, the Tolaki community exhibits contrasting patterns of interfaith relations in the districts of Lambuya and Wolasi. This study employs an interpretive paradigm and a phenomenological approach. The analysis integrates Moustakas' phenomenological framework with the data analysis model developed by Miles and Huberman. Findings reveal that factors such as traditional values, leadership, and shared social practices contribute to harmonious relations in Lambuya, while differing historical contexts and localized social dynamics in Wolasi exacerbate tensions. Additionally, local values such as kolasara and the role of traditional elders are proven to be crucial in maintaining religious harmony in both Lambuya and Wolasi district.